142 Race and Outcomes After Elective Spine Surgery. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Seicean, Andreea; Seicean, Sinziana; Neuhauser, Duncan; Benzel, Edward C.; Weil, Robert John
Abstract: INTRODUCTION: Studies that have looked at the effect of race on spine surgery outcomes have failed to take into account baseline risk factors for adverse outcomes. We wished to determine the effect of race on outcomes in patients undergoing elective laminectomy or fusion. METHODS: We identified 48 493 adult patients who underwent elective laminectomy and/or fusion from 2006 to 2012 at hospitals participating in the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP), a prospectively-collected, national clinical database with established reproducibility and validity. Pre- and intraoperative characteristics and 30-day outcomes were stratified by race. We used propensity scores to match Caucasian and non-Caucasian patients on all pre- and intraoperative factors. We used regular and conditional logistic regression to predict the effect of race on adverse postoperative outcomes in the full sample and matched sample. RESULTS: Caucasians comprised 82% of our sample. We did not find any difference in pre- and intraoperative factors when comparing Caucasian patients to all minority patients, and only minimal increase in odds for prolonged length of hospitalization (LOS) and discharge with continued care. However, African-American (AA) patients, who comprised 39% of our minority sample, had more preoperative comorbidities compared to Caucasian patients. Even after eliminating all differences between pre- and intraoperative factors between Caucasian and AA patients, AA continued to have LOS that was, on average, 1 day longer then Caucasian patients. AA also had higher odds for complications (odds ratio = 1.3; 95% confidence interval: 1.1-1.6) and discharged with continued care (odds ratio = 2.3; confidence interval 1.8-2.8). CONCLUSION: African-American race is an independent predictor of prolonged LOS, complications, and discharge with continued care in patients undergoing elective spine surgery.